2015
DOI: 10.1371/journal.pone.0117393
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Butt Decomposition and Associated Chemical Changes Assessed by 13C CPMAS NMR

Abstract: Cigarette butts (CBs) are the most common type of litter on earth, with an estimated 4.5 trillion discarded annually. Apart from being unsightly, CBs pose a serious threat to living organisms and ecosystem health when discarded in the environment because they are toxic to microbes, insects, fish and mammals. In spite of the CB toxic hazard, no studies have addressed the effects of environmental conditions on CB decomposition rate. In this study we investigate the interactive effects of substrate fertility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 37 publications
4
35
0
2
Order By: Relevance
“…This context-dependency lies in the fact that cellulose filters 221 decomposed much more slowly on the soil surface, while plastic filter decomposition was 222 hardly affected by the disposal environment. This limited context-dependence for plastic 223 filters was previously documented by (Bonanomi et al, 2015) who reported no difference in 224 plastic filter decomposition among different incubation sites varying from sand to grassland. 225…”
Section: Importance Of Disposal Environments 204mentioning
confidence: 54%
See 2 more Smart Citations
“…This context-dependency lies in the fact that cellulose filters 221 decomposed much more slowly on the soil surface, while plastic filter decomposition was 222 hardly affected by the disposal environment. This limited context-dependence for plastic 223 filters was previously documented by (Bonanomi et al, 2015) who reported no difference in 224 plastic filter decomposition among different incubation sites varying from sand to grassland. 225…”
Section: Importance Of Disposal Environments 204mentioning
confidence: 54%
“…Particularly, given the predominant control of environmental 68 conditions on biotic litter decomposition (Berg and McClaugherty, 2008), the decomposition 69 of the cellulose filters is likely to vary widely depending on their disposal environment. In 70 contrast, environmental conditions were shown to have no effect on decomposition of plastic 71 cigarette filters (Bonanomi et al, 2015). Consequently, in composts, where environmental 72 conditions are prone to microbial activity, the relative advantage of cellulose filters over the 73 plastic ones may be reinforced.…”
Section: Abstract 22mentioning
confidence: 98%
See 1 more Smart Citation
“…After concentration by ultrafiltration at 10 kDa, again, correlation in the ACF is still lacking, suggesting that all the carbon materials released from un-CPG are molecular and dissolved or are under the size limit for DLS characterization (evaluated at 1 nm). Because cigarette filters are mostly composed of cellulose-based materials, the release of these materials (degraded or not) is expected (Bonanomi et al, 2015). In contrast, for f-CGB, the increase in the TOC to 4.12±0.24 % (w/CGB) is directly correlated with the distinct exponential decay of the ACF.…”
Section: Resultsmentioning
confidence: 99%
“…This plastic component of filtered cigarettes may not degrade in the environment for many years. Even after deterioration, TPW may persist as small particles of toxic-infused plastic waste, which can leach into soil and water supplies [13]. Slaughter et al showed that 1 cigarette butt soaked in a liter of water for 96 hours reached the Lethal Concentration 50 (LD 50) for test fish exposed to the leachates [14].…”
Section: Introductionmentioning
confidence: 99%